Psycho-neuro-endocrine accompaniments of individual variants of nitrogenous metabolites exchange - Igor Bombushkar; Mykhaylo Korda; Anatoliy Gozhenko; Walery Zukow; Igor Popovych (Kazimierz Wielki University, 2022)
Background. Earlier we showed, by constructing regression models, that plasma nitrogenous metabolites (uric acid, urea, creatinine and bilirubin) are able to influence the state of the trait anxiety, autonomic and central nervous and endocrine systems. In this study of the same cohort, other methodological approaches were used. Materials and Methods. The object of observation were almost healthy volunteers: 30 females (30÷76 y) and 31 males (24÷69 y). In basal conditions determined plasma levels of nitrogenous metabolites as well as cortisol, aldosterone, testosterone, triiodothyronine and calcitonin, estimated the severity of the trait and reactive anxiety, recorded the ongoing HRV and EEG. After 4 or 7 days, repeated testing was performed. Results. By the method of cluster analysis, four groups were created, the members of which differ minimally from each other in terms of the constellation of nitrogenous metabolites, but differ maximally from the members of other groups. Using the method of discriminant analysis, it was found that nitrogenous clusters differ from each other in terms of sex, age, trait anxiety, as well as 30 neuro-endocrine parameters. Conclusion. The obtained data confirm and supplement previous data on the physiological psycho-neuro-endocrine activity of plasma nitrogenous metabolites.